2019
DOI: 10.1016/j.rpor.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of initial electron parameters by means of Monte Carlo simulations for the Siemens Artiste Linac 6 MV photon beam

Abstract: In this study, we investigated initial electron parameters of Siemens Artiste Linac with 6 MV photon beam using the Monte Carlo method.Background: It is essential to define all the characteristics of initial electrons hitting the target, i.e. mean energy and full width of half maximum (FWHM) of the spatial distribution intensity, which is needed to run Monte Carlo simulations. The Monte Carlo is the most accurate method for simulation of radiotherapy treatments.Materials and methods: Linac head geometry was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…To adequately validate the photon beam’s quality taken by the simulation GATE against the accurate measured data and according to international recommendations (IAEA TRS398) [ 15 , 16 ], the index of quality tissue phantom ratio (TPR) in water for the square field 10 × 10 cm 2 the D 10 (%) , d max (cm) and d 80 (cm) are reported and compared as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…To adequately validate the photon beam’s quality taken by the simulation GATE against the accurate measured data and according to international recommendations (IAEA TRS398) [ 15 , 16 ], the index of quality tissue phantom ratio (TPR) in water for the square field 10 × 10 cm 2 the D 10 (%) , d max (cm) and d 80 (cm) are reported and compared as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The Percent Depth Dose (PDD) curves were computed along the central axis. The electron cutoff energy (ECUT) and the photon cutoff energy (PCUT) parameters for the BEAMnrc and DOSXYZnrc were set as 0.7 MeV and 0.01 MeV, respectively (Tuğrul & Eroğul, 2019, 2020. The mean photon energy distribution of X-rays, which were formed as a result of the electron with 6 MeV hitting the target, were obtained by using the 'phase space file' on the BEAMDP (Ma & Rogers, 2020).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…ese steps are ultimately designed to obtain the signi cant parameters in TPS model building. Many investigations have been conducted to benchmark the incident electrons of other medical linear accelerators such as Elekta [3][4][5], Varian [6][7][8][9], and Siemens [10,11], but no dosimetric studies on the XHA600D accelerator have yet been found. And unlike these references, this study speci cally analyzed the e ects of these four incident electron parameters on PDDs and OARs in di erent beam elds and the details of the benchmarking process to obtain accurate incident electron information of the XHA600D accelerator.…”
Section: Introductionmentioning
confidence: 99%